Pengaruh Literasi Keuangan, Gender Dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan Mahasiswa - Yossi Septriani; Lidya Suzanna; Rasyidah Mustika (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2022)
The purpose of this research is to find out empirically relationship between financial literacy, gender and lifestyle with financial management behavior. This research was conducted by taking a sample of accounting students from Politeknik Negeri Padang in West Sumatera. The theory used in this research is Theory of Plan Behaviour theory. Using the Slovin formula and purposive sampling techniques, 90 students were selected as samples. The results of the study that financial literacy did not have a relationship with financial management behavior. Meanwhile, gender and lifestyle has a relationship with financial management behavior. However, simultaneously the three variables, namely financial literacy, gender, and lifestyle have a relationship with financial management behavior.